1981
DOI: 10.1073/pnas.78.12.7689
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal tolerance to alloantigens alters major histocompatibility complex-restricted response patterns.

Abstract: Male-specific transplantation antigen (H-Y)-immune cytotoxic T cells of some individual CBA/H mice exhibit lytic activity on male and female allogeneic targets (e.g., H-2b). Neonatal tolerance to H-2b abrogates the ability of CBA mice to generate secondary H-Y-immune cytotoxic T cells, but such cell activity to third-party alloantigens and to Bebaru and influenza virus is not impaired. The results are discussed in relationship to dominant major histocompatibility complex-coded immune response gene effects on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1982
1982
1992
1992

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
(20 reference statements)
1
8
0
Order By: Relevance
“…Thioglycollate-induced peritoneal exudate cells (PEC) or tumour cell targets (BW (H-2'') from AKR mice. MC57 cells (H-2^), a methylcholanthrene-induced tumour cell line of C57BL/10 origin, and EL4 from C57BL/6 mice, and L929 from C3H mice) grown in vitro were infected with influenza, Sendai, or vaccinia virus and labelled with ' ""^Cr, as deseribed in detail elsewhere [13,15,17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thioglycollate-induced peritoneal exudate cells (PEC) or tumour cell targets (BW (H-2'') from AKR mice. MC57 cells (H-2^), a methylcholanthrene-induced tumour cell line of C57BL/10 origin, and EL4 from C57BL/6 mice, and L929 from C3H mice) grown in vitro were infected with influenza, Sendai, or vaccinia virus and labelled with ' ""^Cr, as deseribed in detail elsewhere [13,15,17].…”
Section: Methodsmentioning
confidence: 99%
“…There now exists good evidence that self H-2-restricted cytotoxic T cells (Tc) specific for minor histocompatibility antigens [3,13] and those specific for viral antigens [18,20] crosstyse unmodified allogeneic targets. Furthermore, alloreactive Tc cells can lyse trinitrophenyl (TNP)-modified self, although such cross-reactivity is not usually observed on virus-infected self targets [15,19].…”
mentioning
confidence: 99%
“…We also tested the hypothesis that natural self-tolerance to K k caused suppression of responses by anti-vaccinia-D b Tc cell precursors, following the precedent for regulation of anti-H-Y Tc cells (17). Considerable evidence consistent with this idea was obtained.…”
Section: Discussionmentioning
confidence: 93%
“…5tCr-release Cytotoxicity Assay. The methods used for the cell lines and macrophage targets have been described in detail elsewhere (12,17). The duration of the assays was 6-12 h. The percent specific lysis was calculated using the formula: percent specific lysis = [(experimental release -medium release)/(maximum release -medium release)] X 100.…”
Section: Strains Of Mice Usedmentioning
confidence: 99%
“…Experiments recently reported by Mullbacher (35) showed that neonatally induced tolerance to H-2 b eliminated the ability of adult CBA (H-2 k) mice to make an H-2 krestricted anti-H-Y response. This was true for 100% of neonatally tolerized animals, even though the anti-H-Y response is crossreactive with H-2 b in only 10-20% of normal adult CBA mice.…”
Section: The Possibility Of Positive Suppression Operating On the H-2mentioning
confidence: 97%